IMPLEMENTATION OF SALES OPERATIONAL AUDITS MEASURING THE EFFECTIVENESS AND EFFICIENCY OF THE SALES FUNCTION IN PT. BERLINA Tbk PANDAAN - ENNY ISTANTI (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: to determine sales in order to measure efficiency and effectiveness at PT. BERLINA Tbk by implementing an operational audit and to determine the level of operational success so as to increase the effectiveness and efficiency of the company. Design/methodology/approach: A qualitative approach is defined as a research procedure that produces descriptive data in the form of written or oral data regarding the actual conditions in the field (companies), then compared with existing theories. The purpose of descriptive research is to make a descriptive, automatic, factual picture or painting of the phenomenon being investigated by analyzing the factors that cause the occurrence or emergence of a phenomenon. Finding: PT. BERLINA Tbk, operational audit has been adequate, the implementation of operational audit in supporting the effectiveness and efficiency of sales at PT. BERLINA Tbk, can be seen from the implementation of sales activities based on policies, systems and sales procedures.In the comprehensive sales procedure, it was found that the sales procedures applied so far were less effective, efficient, and economical because many documents were used and the sales procedures were too complicated. The information system used by the company has not yet been achieved effectively, efficiently and economically. On credit sales due to the unavailability of a credit function to authorize sales orders. Practical implications: Auditing sales operations to measure the effectiveness and efficiency of the sales function Originality/value: This paper is original Paper Type: research paper Keywords : Sales Operational Audit, Effectiveness, Efficiency and Sales